Design, Parameterization, and Implementation of Atomic Force Fields for Adsorption in Nanoporous Materials. Issue 11 (23rd September 2019) - Dubbeldam, David; Walton, Krista S.; Vlugt, Thijs J. H.; Calero, Sofia
Abstract: Molecular simulations are an excellent tool to study adsorption and diffusion in nanoporous materials. Examples of nanoporous materials are zeolites, carbon nanotubes, clays, metal‐organic frameworks (MOFs), covalent organic frameworks (COFs) and zeolitic imidazolate frameworks (ZIFs). The molecular confinement these materials offer has been exploited in adsorption and catalysis for almost 50 years. Molecular simulations have provided understanding of the underlying shape selectivity, and adsorption and diffusion effects. Much of the reliability of the modeling predictions depends on the accuracy and transferability of the force field. However, flexibility and the chemical and structural diversity of MOFs add significant challenges for engineering force fields that are able to reproduce experimentally observed structural and dynamic properties. Recent developments in design, parameterization, and implementation of force fields for MOFs and zeolites are reviewed. Abstract : The flexibility and chemical diversity of nanoporous materials like metal‐organic frameworks (MOFs) poses significant modeling challenges. Much of the reliability of modeling predictions depends on the accuracy and transferability of the used force field. The design, parameterization, and implementation of force fields that lie at the foundation of computing adsorption and diffusion in nanoporous materials are reviewed.